Makna Budaya Lokal Dalam Iklan Sari Roti Kajian Dengan Propaganda Kultura - Casilas, Rara; Suryasuciramdhan, Arfian; S, Sutikah; Safitri, Nur Oktaviani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In the midst of globalization and media developments, advertising not only functions as a promotional tool, but also as a means of conveying culture. This study aims to analyze the meaning of local culture in Sari Roti advertisements using Roland Barthes’ semiotic approach and cultural propaganda theory. The study was conducted using a descriptive qualitative method, analyzing cultural elements such as traditional symbols, language, and social interactions in advertisements. The results of the analysis show that Sari Roti advertisements not only display local values, but also build narratives that strengthen Indonesian cultural identity. This advertisement becomes a medium that conveys ideology symbolically and fosters a sense of nationalism through local products.